The Effect of Capital Structure and Company Growth on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange - Hardianti Pertiwi; Nurfaisah Nurfaisah; Rifqiansyah Rifqiansyah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
The aims of this research are to know and analyze the influence of capital structure, company growth, and profitability on the value of manufacturing companies in the Indonesia Stock Exchange. Populasi dalam penelitian ini adalah seluruh perusahaan manufaktur sektor industri barang konsumsi yaitu sebanyak 42 perusahaan dan jumlah sampel sebanyak 12 perusahaan dengan metode The population in this study were all manufacturing companies in the consumer goods industry sector, namely 42 companies and a total sample of 12 companies using the method purposive sampling .purposive sampling. Penelitian ini menggunakan data sekunder yang berasal dari laporan keuangan tahunan perusahaan manufaktur di Bursa Efek Indonesia .This study uses secondary data derived from the annual financial statements of manufacturing companies in the Indonesia Stock Exchange. Data dianalisis dengan menggunakan program Statistical Packages for Social Science (SPSS).Data were analyzed using the Statistical Packages for Social Science (SPSS) program.Hasil penelitian ini menunjukkan bahwa struktur modal dan profitabilitas berpengaruh negatif dan tidak signifikan terhadap nilai perusahaan manufaktur di Bursa Efek Indonesia . The results of this study indicate that the capital structure and profitability have a negative and not significant effect on the value of manufacturing companies in the Indonesia Stock Exchange . Pertumbuhan perusahaan berpengaruh positif dan tidak signifikan terhadap nilai perusahaan manufaktur di Bursa Efek Indonesia. The company's growth has a positive and not significant effect on the value of manufacturing companies in the Indonesia Stock Exchange.